The productivity of Small East African sheep and goats in Malawi - Banda, J.W. (1994)
The total and additional biological productivity of local (LL) and Boer (BB) goats and their crosses (BL) and of the local (LL) and Dorper (DD) sheep and their crosses (DL) were estimated over two kidding seasons at the Lifidzi Goat Breeding Centre, Salima, Central Malawi.The average 12-weeks milk production was 79.0 ( ± 2.0 kg) in goats and 54.5 ( ± 1.3 kg) in sheep. The difference was significant (P<0.001). The yields of LL (73.7 ± 2.5 kg) and BB (78.3 ± 3.8 kg) were similar, but lower (P<0.001) than those of BL does (85.1 ± 2.3 kg). LL, DL and DD ewes produced 41.4 ± 1.8, 53.5 ± 1.6 and 68.7 ± 2.1 kg milk respectively and the differences among these genotypes were significant (P<0.001).The average daily gain (ADO) from birth to 17 weeks of age was 87.0 ( ± 3.5 g) for kids and 128.9 ( ± 2.8 g) for lambs. Milk conversion was 15.6 and 11.9 kg milk/kg liveweight gain in kids and lambs, respectively. The average mortality was 18.9 and 5.3% in kids and lambs respectively.The total apparent biological productivity indices represented by indices I, II and III were, respectively, 16.6, 0.47 and 1.15 kg for goats. For sheep, the corresponding values were 24.9, 0.80 and 1.89 kg. Additional apparent biological productivity represented by indices IV, V and VI were 7.08, 0.204 and 0.495 kg respectively for goats and 6.13, 0.197 and 0.464 kg for sheep. These results suggest that although the two species differ in milk production, the difference in production is not substantial.